The gut microbiota from maintenance hemodialysis patients with sarcopenia influences muscle function in mice - Tang, Jie; Zhang, Hailin; Yin, Lixia; Zhou, Qifan; Zhang, Huipin (Frontiers in Cellular and Infection Microbiology, 2023)
Sarcopenia is a common complication in patients undergoing maintenance hemodialysis (MHD). Growing evidence suggests a close relationship between the gut microbiota and skeletal muscle. However, research on gut microbiota in patients with sarcopenia undergoing MHD (MS) remains scarce. To bridge this knowledge gap, we aimed to evaluate the pathogenic influence of gut microbiota in the skeletal muscle of patients with MS, to clarify the causal association between gut microbiota and skeletal muscle symptoms in patients with MS and identify the potential mechanisms underlying this causal association.Methods: Fecal samples were collected from 10 patients with MS and 10 patients without MS (MNS).Bacteria were extracted from these samples for transplantation. Mice (n=42) were randomly divided into three groups and, after antibiotic treatment, fecal microbiota transplantation (FMT) was performed once a day for 3 weeks. Skeletal muscle and fecal samples from the mice were collected for 16S rRNA gene sequencing and for histological, real-time PCR, and metabolomic analyses.Results: Mice colonized with gut microbiota from MS patients exhibited notable decreases in muscle function and muscle mass, compared with FMT from patients with MNS. Moreover, 16S rRNA sequencing revealed that the colonization of MS gut microbiota reduced the abundance of Akkermansia in the mouse intestines. Metabolome analysis revealed that seven metabolic pathways were notably disrupted in mice transplanted with MS microbiota.This study established a connection between skeletal muscle and the gut microbiota of patients with MS, implying that disruption of the gut microbiota may be a driving factor in the development of skeletal muscle disorders in patients undergoing MHD. This finding lays the foundation for understanding the pathogenesis and potential treatment methods for sarcopenia in patients undergoing MHD.